2002
DOI: 10.1073/pnas.261715899
|View full text |Cite
|
Sign up to set email alerts
|

The TRAP/Mediator coactivator complex interacts directly with estrogen receptors α and β through the TRAP220 subunit and directly enhances estrogen receptor function in vitro

Abstract: Target gene activation by nuclear hormone receptors, including estrogen receptors (ERs), is thought to be mediated by a variety of interacting cofactors. Here we identify a number of nuclear extractderived proteins that interact with immobilized ER ligand binding domains in a 17␤-estradiol-dependent manner. The most prominent of these are components of the thyroid hormone receptor-associated protein (TRAP)͞Mediator coactivator complex, which interacts with ER␣ and ER␤ in both unfractionated nuclear extracts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
113
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 32 publications
9
113
1
Order By: Relevance
“…In addition, a recent report has shown that the TRAP complex can be purified from HeLa cell nuclear extracts using GST-ER␣ LBD in the presence of agonist ligand (50). In contrast to reports suggesting that TRAP170 interacts with steroid receptors, GST-ER␣ AF1 did not retain TRAP complex in HeLa cell nuclear extracts (50). Thus, recruitment of TRAP complexes to the promoters of estrogen-regulated genes may involve additional interactions with other components of this multiprotein complex.…”
Section: Trap220 Nuclear Receptor Binding Specificitymentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, a recent report has shown that the TRAP complex can be purified from HeLa cell nuclear extracts using GST-ER␣ LBD in the presence of agonist ligand (50). In contrast to reports suggesting that TRAP170 interacts with steroid receptors, GST-ER␣ AF1 did not retain TRAP complex in HeLa cell nuclear extracts (50). Thus, recruitment of TRAP complexes to the promoters of estrogen-regulated genes may involve additional interactions with other components of this multiprotein complex.…”
Section: Trap220 Nuclear Receptor Binding Specificitymentioning
confidence: 83%
“…Purified TRAP/DRIP/mediator complexes have been shown to enhance the activity of NRs in cell-free or purified in vitro transcription assays (17,50,54). In comparison, only very modest enhancement of TR␣/␤, VDR, and PPAR␥-mediated transcription has been observed due to ectopic expression of the NR binding subunit TRAP220/DRIP205/PBP in transiently transfected cells (17, 19 -21).…”
Section: Trap220 Nuclear Receptor Binding Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several coactivator proteins associate with ligand-bound NR and include the p160 proteins, SRC1, TIF2/ GRIP1, and pCIP/ACTR/AIB1/RAC3/TRAM-1 (13). The thyroid hormone receptor-associated protein complex (14), which is very similar to the vitamin D3 receptor-interacting protein complex (15), interacts with liganded NR and is required for thyroid hormone and vitamin D3 receptor as well as ER␣ activities in vitro (16). CBP and the highly related p300, which copurify with RNA polymerase II (17) and associate with p160 coactivators, can directly interact with NR (18 -20).…”
mentioning
confidence: 99%